2017
DOI: 10.3390/proteomes5040036
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omic Biogeography of the Gastrointestinal Microbiota of a Pre-Weaned Lamb

Abstract: The digestive functions of the pre-weaned lamb gastrointestinal tracts (GITs) have been the subject of much research in recent years, but the microbial and host functions underlying these complex processes remain largely unknown. Here, we undertook a proof-of-principle metaproteogenomic investigation on luminal and mucosal samples collected from 10 GITs of a 30-day-old pre-weaned lamb. We demonstrate that the analysis of the diverse ecological niches along the GITs can reveal microbiota composition and metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…3 ). This finding agrees with a research study that revealed that other Firmicutes members showing a great abundance in lamb’s gut were Lachnospiraceae ( Palomba et al 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…3 ). This finding agrees with a research study that revealed that other Firmicutes members showing a great abundance in lamb’s gut were Lachnospiraceae ( Palomba et al 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…Activity-based probe enrichment has been applied in a metaproteomic study of the gut microbiome and was effective in identifying additional set of microbial proteins and revealing protein changes that were not seen in unenriched samples . In addition, different intestinal segments of mammalians harbor different compositions of microbiota; , therefore, the isolation of microbiomes from different regions of gastrointestinal tract might provide another way to simplify the metaproteome by examining a specific set of microbes.…”
Section: Coverage Of Metaproteomicsmentioning
confidence: 99%
“…The absence of a dominant genus in the jejunum, which is highly diverse with 222 genera compared to 185 in the rumen, indicates that its microbiome aids in breaking down numerous small molecules from the food digested by duodenal enzymes before their transport from the jejunum to the liver (Palomba et al, 2017), also significantly increased the diversity of species and abundance of microbes which used different carbohydrates benefit the growth and immune function of the gastrointestinal tract (Cui et al, 2020).…”
Section: Discussionmentioning
confidence: 99%